ENVIRONMENTAL EDUCATION IN THE DISASTER RISK MANAGEMENT PROCESS - Ribeiro, Jefferson; Vieira, Rafaela; Novaes, Jéssica Marciélly de (Geosaberes, 2020)
In the Hydrographic Basin Itajai River/ SC (HBIR) disasters of great magnitude are frequent, among them those occurred in 1983/84 and 2008. The objective of this research is to analyze the contribution of Environmental Education (EE) to Disaster Risk Management (DRM) in municipalities of BHRI. It is descriptive and explanatory, of a qualitative and quantitative nature. It is based on the method of systemic approach and uses techniques of direct documentation (field research) and indirect (documentary and bibliographic research). The results obtained were: (1) identification of innovative national and international strategies that use Information and Communication Technologies (ICT) in AD actions for DRM; (2) critical analysis of the objects and strategies used in the actions of EA for GRD in BHRI; (3) indication of innovative strategies incorporating ICTs that enhance the EE actions implemented at HBIR.